FOIL Method
(5k + 2)(2k - 3) = 10k² - 15k + 4k - 6 = 10k² - 11k - 6
F = 2k x 5k = 10k²
O = 5k x -3 = - 15k
I = 2 x 2k = 4k
L = -3 x 2 = - 6
The answer is 10k² - 11k - 6
- - - - - s-
2006-11-21 23:43:34
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
All the solutions offered give a 'how', but no 'why'. Think about this:-
If 5k + 2 = y,
the question becomes
y(2k-3) which is a simple expansion yielding 2ky -3y.
Substitute for ' y ' ,
2ky - 3y = 2k(5k + 2) -3(5k + 2),
and expanding gives:-
10k^2 + 4k -15k -6 = 10k^2 - 11k -6
That is the ' why ' now the practical how is (and the order doesn't matter) :-
(5k+2)(2k-3) = 5k(2k - 3) + 2(2k - 3)
= 10k^2 - 15k + 4k - 6
= 10k^2 -11k - 6.
That first line is the important one, remember your rules for mult of positives and negatives. Write each step as I have and you will get it right every time. DO NOT TRUST YOURSELF TO DO BITS IN YR HEAD. The ' = ' should all be directly under each other, this system looses the formatting!
2006-11-22 02:22:39
·
answer #2
·
answered by Robert H 2
·
0⤊
0⤋
Use the technique called foil. First Inside Outside Last.
multiply the first two terms 5k(2k) = 10k^2
multiply the two inside terms 5k(-3) -15k
multiply the the two outside terms 2(2k) = 4k
multiply the two last terms 2 * -3 = -6
you now have 10k^2-15k+4k-6, combine all like terms and now you have 10k^2-11k-6
2006-11-22 00:10:17
·
answer #3
·
answered by ayok 2
·
1⤊
0⤋
Remember FOIL
First: 5k * 2k = 10k^2
Outside: 5k * -3 = -15k
Inside: 2 * 2k = 4k
Last: 2 * -3 = -6
Add all those answers up: 10k^2 -15k+4k-6
Simplified: 10k^2-11k-6
2006-11-22 00:09:06
·
answer #4
·
answered by MikeC 3
·
2⤊
0⤋
of course i can! I love this type of problem, it's called F-O-I-L which stands for (First, Outer, Inner, Last) this stands for the order you multiply the terms in:
Your problem reads (5k+2)(2k-3) here's your steps:
Step 1: Multiply the FIRST TERMS in each set of parenthesis: 5k*2k= 10k^2 (I don't know how to say it's squared, but it reads 10k-squared)
Step 2: Multiply the OUTER TERMS in each set of parenthesis:
5k*-3= -15K
Step 3: Multiply the INNER TERMS in each set of parenthesis:
2*2k= 4k
Step 4: Multiply the LAST TERMS in each set of parenthesis:
2*-3= -6
Then, after you get all of your answers, write them in a line
10k^2-15k+4k-6 and combine like terms
10k^2-11k-6 and that is your answer!!!
GOOD LUCK!!
2006-11-22 01:01:31
·
answer #5
·
answered by Buckwild 2
·
0⤊
0⤋
Step1: Multiply the two first terms in each of the parenthesis together. In this case 5k and 2k.
Step2: Multiply the two outer terms, the terms outside within the parenthesis. In this case 5k and -3.
Step3: Multiple the two inner terms, the terms deep inside the parenthesis. In this case 2 and 2k.
Step4: Multiply the two last terms, the terms that are last in each of the parenthesis. In this case the 2 and the -3.
Once you have all the products, you combine the like terms.
2006-11-22 00:12:56
·
answer #6
·
answered by ? 4
·
1⤊
0⤋
well if you're trying to expand the brackets..
i use the FOIL method which stands for FIRST, OUTER, INNER, LAST
in the sum (5k+2)(2k-3) you would times 5k and 2k first, then 5k and -3, then 2 and 2k, and finally 2 and -3
you would then get 10k2-15k+4k-6
then simplify it to 10k2-11k-6
2006-11-22 00:09:42
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
take 5k times (2k-3) and 2 times (2k-3)
10k^2-15k+4k-6
ans: 10k^2-11k-6
2006-11-22 00:04:40
·
answer #8
·
answered by 7
·
2⤊
0⤋
(5k+2)(2k-3) use FOIL firt, outside, inside last.
1st: 10k^2
out: -15k
in: 4k
last: -6 add them all up
10k^2-11k-6
2006-11-22 00:21:30
·
answer #9
·
answered by yupchagee 7
·
1⤊
0⤋
(5k+2)(2k-3)
5k(2k-3) +2(2k-3)
(10k^2-15k)+(4k-6)
10k^2-11k-6
2006-11-22 06:57:32
·
answer #10
·
answered by Hana 2
·
0⤊
0⤋